Causality between foreign aid and life expectancy in Zimbabwe - Kondo, Talent; Mutsvangwa , Simba; Mandishekwa , Robson (Journal of Social, Humanity, and Education, 2025)
Purpose: To investigate the causal relationship between foreign aid and life expectancy in Zimbabwe. Research methodology: This study employed a Granger causality test to analyze the causal relationship between foreign aid and life expectancy for the period–1980-2019. Results: This study revealed that there is no causal relationship between foreign aid and life expectancy in Zimbabwe. Conclusions: This study focuses on the causal relationship between foreign aid and life expectancy in Zimbabwe. This finding reveals that aid does not improve life expectancy. Policies for Zimbabwe should not focus much on improving life expectancy by relying mostly on foreign aid, but through domestic financing. Limitations: The study's limitations include potential factors that may not have been included, which could impact the relationship between aid and life expectancy. These results are specific to Zimbabwe and may not be generalizable to other countries. Contribution: This study offers valuable insights to the government and other stakeholders in formulating evidence-based policies aimed at optimizing the utilization of foreign aid. Specifically, these findings can inform the design of targeted health policies with the potential to positively influence life expectancy outcomes in Zimbabwe. Novelty: While previous research has often focused on broad economic indicators, this study uniquely emphasizes health outcomes, specifically life expectancy, as a key measure of development. This study highlights the critical issues of aid mismanagement and corruption, advocating for greater transparency and accountability in the usage of foreign aid.